MENINGKATKAN NILAI RASA DAN ESTETIKA BAHAN MASAKAN LOKAL SEBAGAI DAYA TARIK BAGI WISATAWAN PULAU TUNDA - Nila Prasetyo Artiwi (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat Universitas Banten Jaya, 2020)
Tunda Island is a group of 17 islands in Serang Regency, Banten Province. Administratively, Tunda Island is located in Tirtayasa District, Serang Regency, Banten Province. Seen geographically, Pulau Tunda is located at coordinates 5 ° 48 '43' 'latitude and 106 ° 16' 47 ''. Tunda Island has become a very attractive tourism object because it has beautiful beaches and sea that can be explored as an attraction for tourists. The Banten Jaya University Research and Community Service Institute (LP3M) has won the trust of the Serang Regency Youth Sport and Tourism Service (Disporapar) as a companion to the Tunda Island Tourism Village to improve the quality of human resources in the tourism sector (Kabar Banten, 21/09/2020). The cooking demonstration activity is assisted by an experienced chef in order to increase human resource resources in the tourism sector and in order to increase the taste and aesthetic value of the local Tunda Island cuisine ingredients as an attraction in the form of offerings to Tunda Island tourists. As a result, the people of Tunda Island get knowledge and new menu alternatives from local food ingredients.